MEIGS SYNDROME MIMICKING MALIGNANCY: A DIAGNOSIS CHALLENGE - Ratri Wulandari; Yosi Tamara (Jurnal Kedokteran Diponegoro, 2025)
Background: Meigs syndrome is a benign ovarian mass associated with pleural effusion and ascites. The ovarian tumor is typically a fibroma, the most common benign pure stromal tumor, with 10-15% of cases presenting with pleural effusion or ascites. Case Presentation: Here, we present a Meigs syndrome in a 57-year-old woman. This patient complained of an abdominal mass and massive pleural effusion. Multiple uterine myomas and left ovarian solid tumor were found during laparotomy. Following the removal of ovarian mass, the patient’s condition improved, and she was discharged a week after being hospitalized. Conclusion: The clinical symptoms of Meigs syndrome are similar to those of malignant disease. However, with optimal treatment, the outcome of Meigs’s syndrome is generally satisfactory.